Virulensi Cendawan Entomopatogen Aspergillus spp.Sebagai Agen Biokontrol Hama Rayap Coptotermes curvignathus (Isoptera: Rhinotermitidae) - Oviana Lisa; Syaukani Syaukani; Lenni Fitri; Putri Mustika Sari; Siti Aminah; Ernilasari Ernilasari (Jurnal Agrotek Lestari, 2023)
The termite Coptotermes curvignathus is an important pest in oil palm plantations and environmentally friendly control measures are needed. The fungus Aspergillus spp. has potential as a biocontrol agent against the termite C. curvignathus. The purpose of this study aimed to obtain Aspergillus spp. which are virulent against C. curvignathus. Aspergillus spp. isolates used in this study were collected from termite nests in the primary forest at Suaq Balimbing Research Station, Gunung Leuser National Park, Sumatra. This study used an experimental method with a completely randomized design (CRD). Two isolates of Aspergillus spp. each 105 conidia/mL were applied to worker caste termites. The results of the virulence assay showed that isolate Aspergillus sp. 1 had the highest causing 82.13% mortality of C.curvignathus and with  an LT50 value of 4.18 days.